A dynamic model of CT scans for quantifying doubling time of ground glass opacities using histogram analysis - József Z. Farkas; Gary T. Smith; Glenn F. Webb (Mathematical Biosciences and Engineering)
We quantify a recent five-category CT histogram based classification of ground glass opacities using a dynamic mathematical model for the spatial-temporal evolution of malignant nodules. Our mathematical model takes the form of a spatially structured partial differential equation with a logistic crowding term. We present the results of extensive simulations and validate our model using patient data obtained from clinical CT images from patients with benign and malignant lesions.